Thermoplastic composite material

The semi-aromatic polyamide particles with suitable design were prepared by melt extrusion method, and these particles were used in the slurry impregnation method, which solved the problems of uneven distribution of thermoplastic polymers and slow production speed in the composite material, and achieved high mechanical properties and efficient production of the composite material.

CN119585345APending Publication Date: 2025-03-07SOLVAY SPECIALTY POLYMERS USA LLC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380055260.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-24
Filing Date
2023-07-18
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prior art is difficult to uniformly heat and distribute the materials of thermoplastic polymers in the mold and at the mold outlet, resulting in poor quality and uniformity of the composite material, and high viscosity thermoplastic resins limit high fiber content and production speed.

Method used

Semi-aromatic polyamide particles with suitable design average particle size, particle size distribution and shape are prepared by melt extrusion method, using these particles to prepare composite materials in a slurry impregnation method.

Benefits of technology

The uniform distribution and efficient preparation of semi-aromatic polyamide particles are achieved, and the mechanical properties and production efficiency of composite materials are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005251424620000201
    Figure BDA0005251424620000201
  • Figure FDA0005251424610000011
    Figure FDA0005251424610000011
  • Figure FDA0005251424610000012
    Figure FDA0005251424610000012
Patent Text Reader

Abstract

There is provided a set of particles made from a thermoplastic composition comprising at least one semi-aromatic polyamide, the particles having a volume-based median particle size D (v, 0.5) of 0.1 to 50.0 [mu] m and an asymmetric particle size distribution. The set of particles is suitable for preparing a composite material comprising continuous fibers by a slurry impregnation process.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to U.S. Provisional Patent Application No. 63 / 391,349 filed on July 22, 2022 and European Patent Application No. 22191834.5 filed on August 24, 2022, both of which are incorporated herein by reference in their entirety for all purposes. Technical Field

[0003] The present invention relates to a thermoplastic composite tape comprising a semi-aromatic polyamide and continuous fibers, as well as to semi-aromatic polyamide particles and a composition for making said tape. Background Art

[0004] Composite materials comprising structural reinforcement fibers embedded in a polymer matrix are used in a variety of applications. For example, composite materials comprising continuous fibers have been used to form fiber-reinforced composite tapes, strips, rods, prepregs, laminates, and profiles that can be used as lightweight structural reinforcement components in many applications. Composite materials comprising thermoplastic polymer matrices are known to provide many benefits compared to thermosetting base materials. For example, thermoplastic tapes or prepregs can be manufactured into articles more quickly. Another advantage is that thermoplastic articles can be recycled.

[0005] Thermoplastic composites containing continuous fibers can be produced by impregnating continuous fibers, typically carbon or glass fibers, usually using one of two methods: melt impregnation or slurry impregnation.

[0006] Melt impregnation uses a combination of conventional melt processing equipment and a dedicated die for combining the molten polymer with the fibers and ensuring uniform distribution of the polymer within the spread fibers. This method has the following disadvantages: it is difficult to uniformly heat the molten mixture of thermoplastic polymers in the die and at the die outlet to the core of the material, which changes the quality of the impregnation. In addition, the difference in the existing temperature between the fiber and the molten mixture of polymer at the level of the impregnation die also changes the quality and uniformity of the impregnation. In addition, due to the high viscosity of thermoplastic resins, especially when they have a high glass transition temperature, this mode of self-melt impregnation makes it impossible to obtain high fiber content or high production speed, which is necessary for obtaining high-performance composite materials.

[0007] Slurry impregnation differs in that, although a die is sometimes still used, the impregnation step occurs by passing the continuous fibers through an actively mixed aqueous colloidal suspension containing the polymer. This suspension typically contains both polymer particles and water, and active mixing prevents settling of the polymer particles.

[0008] For example, US 4292105 discloses a method for impregnating a fibrous textile material with a plastic resin, the method comprising forming a dispersion of a powdered plastic resin in water in the presence of a water-soluble thickener; applying the dispersion to the fibrous textile material to distribute the resin on the fibers; drying the impregnated fibrous textile material to remove the water present; and heating the dried material to cause the resin to melt and form a matrix for the fibers. US 4292105 confirms that the penetration of the powdered plastic resin between the filaments of the fibrous material can be promoted by using particles with a size less than 50 microns and particularly particles with a diameter close to the diameter of the filaments of the fibrous material. However, the working examples in US 4292105 only disclose the use of plastic resin particles having a size that allows them to pass through a 177 or 250 micron sieve. In addition to screening, US 4292105 does not provide a suitable method for preparing the particles. Furthermore, US 4292105 does not acknowledge the importance of using particles having a uniform distribution of particle size and / or shape in a process for preparing composite materials via a slurry impregnation process and therefore does not disclose a process for preparing said particles starting from a wide range of polymers.

[0009] Grinding or milling can provide a way to obtain polymer particles of suitable size. However, the ground particles tend to have irregular and often jagged edge shapes and a wide particle size distribution. The irregular particle shape may lead to poor powder flow properties during the tape impregnation process. In addition, powder particles with shape irregularities may provide poor packing efficiency after deposition and consolidation, thereby causing extensive void formation in the final composite tape due to the powder particles not being tightly packed together during deposition.

[0010] There are additional complications for producing powders from polymers with low crystallinity, low glass transition temperature, and / or high toughness. In other words, these attributes hinder the powder production process. For example, during the grinding process, high polymer ductility causes particle shape changes (i.e., flattening) rather than size reduction. Even when using cryogenic grinding techniques (which are methods for making the grinding temperature below the glass transition temperature of the polymer in order to alleviate the problem of high polymer ductility), it is still difficult to achieve a small particle size distribution.

[0011] Therefore, there still exists a need to provide polymer particles to be used in aqueous slurries to prepare composite materials via an impregnation process and having an average particle size in the range of 0.1 to 50.0 microns and a regular shape. In particular, there exists a need to provide such particles made from polymers having a low glass transition temperature and / or high toughness, as small particle sizes are difficult to obtain by mechanical milling due to the tendency of the particles to stick to the milling equipment.

[0012] Semiaromatic polyamides are polymers that, due to their excellent mechanical properties, may ideally provide a suitable polymer matrix for composite materials, but these polymers suffer from the limitation detailed above that they are difficult to obtain in the form of powders comprising particles having an average size of 0.1 to 50.0 microns and a regular shape.

[0013] Additionally, semi-aromatic polyamide polymers partially or fully derived from renewable resources and meeting the above requirements are even more desirable since they provide an environmentally friendly solution. Summary of the invention

[0014] In order to provide a method for preparing a composite material comprising a semi-aromatic polyamide using a slurry impregnation method, the inventors have discovered that a semi-aromatic polyamide powder comprising particles having an average particle size, a particle size distribution and a shape suitable for designing a slurry impregnation method can be prepared using a melt extrusion method. In the method, a thermoplastic polymer and a material that is immiscible with the thermoplastic polymer but is generally soluble in a given solvent are typically mixed in an extruder at a temperature greater than the melting point or softening temperature of the thermoplastic polymer and at a sufficiently high shear rate to disperse the thermoplastic polymer in the immiscible material; the molten mixture is then cooled to below the melting point or softening temperature of the thermoplastic polymer to form solidified particles comprising thermoplastic polymer particles; the solidified particles are then separated from the immiscible material, typically by dissolving the immiscible material in an appropriate solvent. DETAILED DESCRIPTION

[0015] In this application:

[0016] - even any description related to a specific embodiment is applicable to and interchangeable with other embodiments of the present disclosure;

[0017] - When an element or component is said to be included in and / or selected from a list of listed elements or components, it should be understood that in the relevant embodiments explicitly considered herein, the element or component may also be any of these listed independent elements or components, or may also be selected from a group consisting of any two or more of the explicitly listed elements or components; any element or component listed in the list of elements or components may be omitted from this list;

[0018] - Any recitation of numerical ranges by endpoints herein includes all numbers contained in the recited range as well as the endpoints of that range and equivalents thereof;

[0019] - unless otherwise stated, the terms "a / an", "the" or "the" mean "one / one or more / a plurality of" or "at least one / one" and are used interchangeably; and

[0020] - The term "and / or" used in a phrase in the form "A and / or B" means A alone, B alone, or A and B together.

[0021] A first object of the present invention is a collection of particles, wherein the particles consist of a thermoplastic composition comprising at least one semi-aromatic polyamide; and wherein the particles have a volume-based median particle size D(v,0.5) of 0.1 to 50.0 μm and a particle size distribution such that the following relation (I) is satisfied:

[0022] (I)

[0023] Where D(v,0.9) is the particle size below which 90% of the sample lies; D(v,0.5) is the particle size below which 50% of the sample lies and 50% of the sample lies above this size; and D(v,0.1) is the particle size below which 10% of the sample lies.

[0024] Thermoplastic composition

[0025] The thermoplastic composition comprises at least one semi-aromatic polyamide. The expression semi-aromatic polyamide refers to a polyamide comprising repeating units derived from at least one aromatic monomer and at least one aliphatic monomer. The aromatic monomer may be a diamine, a diacid or an amino acid.

[0026] In an embodiment, the semi-aromatic polyamide may include repeating units derived from an aromatic diamine.

[0027] The semi-aromatic polyamide may comprise at least 50 mol %, typically at least 70 mol %, of recurring units derived from aromatic diamines, relative to the total amount of diamine units in the polyamide.

[0028] Preferably, the semi-aromatic polyamide comprises repeating units derived from aromatic diamines having 6 to 18 carbon atoms.

[0029] Examples of suitable C6-C18 aromatic diamines include, but are not limited to, metaphenylenediamine (MPD), paraphenylenediamine (PPD), 3,4'-diaminodiphenyl ether (3,4'ODA), 4,4'-diaminodiphenyl ether (4,4'-ODA), paraxylene diamine (PXD), and metaxylene diamine (MXD).

[0030] Notable non-limiting examples of suitable polyamides containing aromatic diamines are polyamides such as those containing repeating units of the formula MXDZ, wherein Z represents a unit derived from a linear or branched aliphatic or alicyclic diacid having z carbon atoms, wherein z is an integer equal to or greater than 6 and MXD is meta-xylene diamine. Z is preferably selected from aliphatic diacids having 6 to 16 carbon atoms. Notable non-limiting examples are adipic acid, sebacic acid or dodecanedioic acid. More preferably, Z is adipic acid.

[0031] In some embodiments, the semi-aromatic polyamide may additionally comprise repeating units of the formula PXDZ, wherein PXD represents units derived from p-xylylenediamine and Z is as defined above.

[0032] In certain embodiments, the semi-aromatic polyamide is a polyamide of formula A / MXDZ, wherein A is a repeating unit derived from at least one of the following: an amino acid, i.e. a molecule containing a primary carboxylic acid and a primary amine, a lactam or a unit having the formula (Ca diamine).(Cb diacid), wherein "a" represents the number of carbon atoms of the diamine and "b" represents the number of carbon atoms of the diacid, and wherein "a" and "b" are independently of each other an integer between 4 and 36, advantageously between 6 and 18. Component (Ca diamine) is preferably selected from the group consisting of linear or branched aliphatic diamines, cycloaliphatic diamines and alkyl aromatic diamines. Examples are, for example, hexamethylenediamine, decanediamine, dodecanediamine and MXD.

[0033] The component (Cb diacid) is preferably selected from the group consisting of linear or branched aliphatic diacids, cycloaliphatic diacids and aromatic diacids. Examples are, for example, adipic acid, sebacic acid or dodecanedioic acid or 3-(aminomethyl)benzoic acid (3-AMBa).

[0034] In an advantageous embodiment, the units A or Z may be derived from renewable materials. Non-limiting examples of suitable polyamides of this type are: PA MXD6, PA MXD10.

[0035] In another embodiment, the semi-aromatic polyamide comprises repeating units derived from an aromatic diacid.

[0036] In a preferred embodiment, the semi-aromatic polyamide comprises repeating units of formula XT, wherein X represents a unit derived from a linear or branched aliphatic or cycloaliphatic diamine having x carbon atoms, wherein x is an integer equal to or greater than 6 and T represents a unit derived from terephthalic acid.

[0037] The semiaromatic polyamide comprises at least 50 mol %, typically at least 70 mol %, even at least 90 mol % of recurring units of the formula XT.

[0038] The semi-aromatic polyamide may contain more than one repeating unit of formula XT, wherein each unit X is derived from a different diamine. Alternatively, in addition to the repeating units of formula XT, the semi-aromatic polyamide may also contain repeating units of formula X'T, wherein X' represents a unit derived from a linear or branched aliphatic or alicyclic diamine having x' carbon atoms, wherein x' is an integer lower than 6.

[0039] In some embodiments, the semi-aromatic polyamide may additionally comprise repeating units of formula XI, wherein I represents a unit derived from isophthalic acid and X is as defined above.

[0040] When present, the units X, or the units XI, in formula XT are derived from linear or branched aliphatic or alicyclic diamines having x carbon atoms, x being greater than 6 and up to 36, advantageously between 8 and 18. The units X are preferably derived from aliphatic diamines selected from the group consisting of 1,8-octanediamine, 1,9-nonanediamine, 2-methyl-1,8-octanediamine (Me8), 1,10-decanediamine, 1,12-dodecanediamine, 2,2,4-trimethyl-1,6-hexanediamine, 2,4,4-trimethyl-1,6-hexanediamine, 5-methyl-1,9-nonanediamine, 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, isophoronediamine, and mixtures thereof. In a preferred embodiment of the present invention, the unit X is derived from the group of aliphatic diamines, the group consisting of: 1,8-octanediamine, 1,9-nonanediamine, 2-methyl-1,8-octanediamine, 1,10-decanediamine, 1,12-dodecanediamine and mixtures thereof. More preferably, the unit X is derived from the group of aliphatic diamines, the group consisting of: 1,9-nonanediamine, 2-methyl-1,8-octanediamine, 1,10-decanediamine, 1,12-dodecanediamine and mixtures thereof.

[0041] In certain embodiments, the aliphatic diamines may be derived from renewable materials. Notable non-limiting examples of such diamines are, for example, 1,10-decanediamine and 1,12-dodecanediamine, which may be derived from castor oil.

[0042] Notable non-limiting examples of suitable polyamides comprising only recurring units of formula XT or XT / X'T are PA 6T, PA 8T, PA Me8T, PA 9T, PA Me8T / 9T, PA 10T, PA 11T, PA 12T, PA 6T / 9T, PA 9T / 10T, PA 9T / 11T, PA 9T / 12T, PA 6T / 10T, PA 6T / 11T, PA 6T / 12T, PA 10T / 11T, PA 10T / 12T, PA 11T / 12T.

[0043] In certain embodiments, the semi-aromatic polyamide is a copolyamide of formula Y / XT, wherein XT is as defined above and Y is a repeating unit derived from at least one of the following: an amino acid, i.e. a molecule containing a primary carboxylic acid and a primary amine, a lactam or a unit having the formula (Cn diamine).(Cm diacid), wherein "n" represents the number of carbon atoms of the diamine and "m" represents the number of carbon atoms of the diacid, and wherein "n" and "m" are independently of each other integers between 4 and 36, advantageously between 6 and 18. The component (Cn diamine) is preferably selected from the group consisting of linear or branched aliphatic diamines, cycloaliphatic diamines and alkyl aromatic diamines. The component (Cm diacid) is preferably selected from the group consisting of linear or branched aliphatic diacids, cycloaliphatic diacids and aromatic diacids.

[0044] In an advantageous embodiment, the unit Y in formula Y / XT can be derived from renewable materials. Notable non-limiting examples of diacids or amino acids derived from renewable sources are, for example, sebacic acid or 3-(aminomethyl)benzoic acid (3-AMBa), which can be derived from furfural.

[0045] Notable non-limiting examples of suitable copolyamides of formula Y / XT are polyamides of formula Y / 6T, Y / 9T, Y / 10T or Y / 11T, Y being as defined above. Suitable copolyamides are, in particular, polyamides from the group consisting of PA 10 / 6T, 6PA10 / 9T, PA 10 / 10T, PA 10 / 11T, PA 10 / 12T, PA 11 / 6T, PA 11 / 9T, PA 11 / 10T, PA 11 / 11T, PA11 / 12T, PA 12 / 6T, PA 12 / 9T, PA 12 / 10T, PA 12 / 11T, PA 12 / 12T, PA 610 / 6T, PA 612 / 6T, PA910 / 6T, PA 912 / 6T, PA 1010 / 6T, PA 1012 / 6T, PA 610 / 9T, PA 612 / 9T, PA 910 / 9T, PA 912 / 9T, PA 1010 / 9T, PA 1012 / 9T, PA 610 / 10T, PA 612 / 10T, PA 910 / 10T, PA 912 / 10T, PA 1010 / 10T, PA 1012 / 10T, PA 610 / 12T, PA 612 / 12T, PA 910 / 12T, PA 912 / 12T, PA 1010 / 12T, PA11 / 6T / 9T, PA 11 / 6T / 10T, PA 11 / 6T / 11T, PA 11 / 6T / 12T, PA 11 / 9T / 10T, PA 11 / 9T / 11T, PA11 / 9T / 12T, PA 11 / 10T / 11T, PA 11 / 10T / 12T, PA 11 / 11T / 12T, PA 12 / 6T / 10T, PA 12 / 6T / 11T, PA 12 / 6T / 12T, 12 / 9.T / 10.T, PA 12 / 9T / 11T, PA 12 / 9T / 12T, PA 12 / 10T / 11T, PA 12 / 10T / 12T, PA 12 / 11T / 12T, PA MXDT / 10T, PA MPMDT / 10T, PA BACT / 10T, PA BACT / 6T, PABACT / 10T / 6T.

[0046] The thermoplastic composition may consist of a semi-aromatic polyamide.

[0047] Alternatively, the thermoplastic composition may include one or more additives. Examples of suitable additives include, but are not limited to, fillers, reinforcing agents, pigments, pH regulators, lubricants, heat stabilizers, light stabilizers, antioxidants, processing aids, and combinations thereof. Examples of fillers include, but are not limited to, glass fibers, glass particles, mineral fibers, carbon fibers, oxide particles (e.g., titanium dioxide, silicon dioxide, zinc oxide, cerium oxide, and zirconium dioxide), metal particles (e.g., aluminum powder), talc, wollastonite, calcium carbonate, mica, and any combination thereof. Examples of pigments include, but are not limited to, organic pigments, inorganic pigments, carbon black, and any combination thereof.

[0048] The polymer composition may further comprise flame retardants such as halogen and halogen-free flame retardants.

[0049] The additive may be present in the thermoplastic composition in an amount of 0.1 wt % to about 40.0 wt %, even 1.0 wt % to 35.0 wt %, or 5.0 wt % to 30.0 wt %, relative to the total weight of the thermoplastic composition.

[0050] In certain embodiments, the thermoplastic composition may include one or more thermoplastic polymers other than semi-aromatic polyamides. Examples of suitable polymers include, but are not limited to, impact modifiers. The polymer backbone of the impact modifier may be selected from an elastomeric backbone comprising polyethylene and copolymers thereof, for example, ethylene-butene; ethylene-octene; polypropylene and copolymers thereof; polybutene; polyisoprene; ethylene-propylene-rubber (EPR); ethylene-propylene-diene monomer rubber (EPDM); ethylene-acrylate rubber; butadiene-acrylonitrile rubber, ethylene-acrylic acid (EAA), ethylene-vinyl acetate (EVA); acrylonitrile-butadiene-styrene rubber (ABS), block copolymer styrene ethylene butadiene styrene (SEBS); block copolymer styrene butadiene styrene (SBS); methacrylate-butadiene-styrene (MBS) type core-shell elastomers, or a mixture of one or more of the above.

[0051] When the impact modifier is functionalized, the functionalization of the backbone can result from copolymerization containing functionalized monomers, or from grafting the polymer backbone with another component. Specific examples of functionalized impact modifiers are notably terpolymers of ethylene, acrylate and glycidyl methacrylate, copolymers of ethylene and butyl acrylate; copolymers of ethylene, butyl acrylate and glycidyl methacrylate; ethylene-maleic anhydride copolymers; EPR grafted with maleic anhydride; styrene copolymers grafted with maleic anhydride; SEBS copolymers grafted with maleic anhydride; styrene-acrylonitrile copolymers grafted with maleic anhydride; ABS copolymers grafted with maleic anhydride.

[0052] Functionalized polyolefin impact modifiers are available from commercial sources and include maleated polypropylene and ethylene-propylene copolymers (as PO) and a maleic anhydride functionalized ethylene-propylene copolymer rubber containing about 0.6 weight percent pendant succinic anhydride groups, such as TEFLON® from Exxon Mobil Chemical Company. VA 1801; as Available acrylate-modified polyethylenes are 9920, acrylic acid or methacrylic acid modified polyethylene from Dow Inc.; maleic anhydride modified SEBS block copolymers such as FG1901X, SEBS that has been grafted with about 2 wt % maleic anhydride, available from Kraton Polymers; maleic anhydride functionalized EPDM terpolymer rubber, such as 498, 1% maleic anhydride functionalized EPDM, available from SI Group.

[0053] Other desired functionalized impact modifiers include but are not limited to ethylene-higher alpha-olefin polymers and ethylene-higher alpha-olefin-diene polymers grafted or copolymerized with reactive carboxylic acids or derivatives thereof, such as acrylic acid, methacrylic acid, maleic anhydride or its ester. Suitable higher alpha-olefins include but are not limited to C3 to C8 alpha-olefins, such as propylene, 1-butene, 1-hexene and styrene. Alternatively, the copolymer having a structure comprising such units can also be obtained by hydrogenating a suitable homopolymer and a copolymer of the 1-3 diene monomers of polymerization. For example, polybutadiene with different levels of side-bonded vinyl units is easily obtained, and these can be hydrogenated to provide ethylene-butene copolymer structures. Similarly, equivalent ethylene-isobutylene copolymers can be provided using the hydrogenation of polyisoprene.

[0054] Among the reactive impact modifiers, mention may be made of those marketed under the name AX8900 is a random terpolymer of ethylene, acrylic acid ester and glycidyl methacrylate commercially available from Arkema (Bristol, Pennsylvania, USA). Another example of the above reactive impact modifier is available under the trade name Paraloid TM EXL 2314, commercially available from Dow Company (Midland, Michigan, USA), is a core-shell type acrylate-based impact modifier comprising a core consisting primarily of a crosslinked poly(n-butyl acrylate) rubber and having a shell phase consisting primarily of a poly(methyl methacrylate)-poly(glycidyl methacrylate) copolymer.

[0055] The thermoplastic composition can include at least one impact modifier of 0.5wt% to 25.0wt% relative to the total weight of the composition. The impact modifier can account for at least 1.0wt%, at least 2.0wt% or at least 3.0wt%, even at least 5.0wt% of the total weight of the composition. The impact modifier is typically no more than 20.0wt%, no more than 15.0wt%, no more than 12.0wt%, even no more than 10.0wt%. Suitable ranges can be, for example, 0.5wt% to 15.0wt%, even 0.5wt% to 12.0wt%, or even 2.0wt% to 10.0wt%.

[0056] Particles

[0057] As used herein, the term "particle" refers to an individualized entity.

[0058] The particles have a volume-based median particle size D(v,0.5) of 0.1 to 50.0 μm and a particle size distribution such that the following relationship (I) is satisfied:

[0059] (I)

[0060] In relation (I):

[0061] -D(v,0.9) is the particle size below which 90% of the sample lies;

[0062] - D(v,0.5) is the particle size below which 50% of the sample is smaller and 50% of the sample is larger; and

[0063] - D(v,0.1) is the particle size below which 10% of the sample lies.

[0064] As used herein, unless otherwise indicated, particle size distribution refers to volume distribution. Particle size distribution can be determined according to any method known in the art. In particular, particle size and particle size distribution are determined by laser diffraction of a suspension of particle sets in isopropanol. A MicroTrac S3500 laser diffraction instrument can be used according to the manufacturer's instructions or known methods. Detailed methods are disclosed in the experimental section.

[0065] The particles in the collection of the present invention have a median particle size D(v,0.5) of 0.1 to 50.0 μm, typically 1.0 to 50.0 μm. The median particle size D(v,0.5) can conventionally be at least 1.5 μm, even at least 2.5 μm, still at least 5.0 μm. The average particle size D(v,0.5) can conventionally be less than 50.0 μm, even less than 45.0 μm. In some embodiments, the average particle size D(v,0.5) is 2.5 μm to 40.0 μm, preferably 5.0 μm to 30.0 μm, or 7.5 μm to 25.0 μm.

[0066] The particles may further have a particle size distribution such that D(v,0.9) is 100.0 μm or less, typically 65.0 μm or less, even 50.0 μm or less.

[0067] Additionally, the particles may further have a particle size distribution such that D(v,0.1) is at least 1.0 μm, typically at least 2.5 μm, more typically at least 5.0 μm.

[0068] The present disclosure contemplates any combination of the above-described D(v, 0.1), D(v, 0.5), and D(v, 0.9) ranges.

[0069] The particles of the present invention have a particle size distribution that is asymmetric about the value of D(v,0.5), as shown by the relationship (I):

[0070] (I)

[0071] In certain embodiments, the particle size distribution is such that the relationship (Ia) is satisfied:

[0072] (Ia)

[0073] even:

[0074] (Ib)

[0075] The particle size distribution may be such that the following relationship (II) is also satisfied:

[0076] (II)

[0077] Without wishing to be bound by theory, it is believed that a particle size distribution skewed towards larger particle sizes is advantageous in preparing continuous fiber composites via a slurry impregnation process because it reduces the risk of blistering that may be caused by particles having smaller diameters when forming the slurry.

[0078] Advantageously, these particles are characterized by a combination of the following properties:

[0079] - D(v,0.5) is 0.1 to 50.0 μm, typically 1.0 to 50.0 μm, 2.5 to 40.0 μm, preferably 5.0 to 30.0 μm, even 7.5 to 25.0 μm; and

[0080] - typically

[0081] even

[0082] as well as

[0083] - and / or

[0084] - D(v,0.9) is 100.0 μm or less, typically 65.0 μm or less, even 50.0 μm or less; and / or

[0085] - D(v,0.1) is at least 1.0 μm, typically at least 2.5 μm, more typically at least 5.0 μm.

[0086] The particles preferably have a regular shape, ie they are substantially round.

[0087] In aspects of the invention, the particles are characterized by an aspect ratio of 0.8 to 1.3. The aspect ratio is defined as the ratio of the longest dimension to the shortest dimension of the particle, as determined by image analysis of photographs of a collection of particles taken by scanning electron microscopy, as detailed in the experimental section.

[0088] Method for making particles

[0089] The collection of particles consisting of the thermoplastic composition as detailed above can be prepared according to a melt extrusion process, wherein a thermoplastic composition and a soluble material immiscible with the thermoplastic composition are typically mixed in an extruder at a temperature greater than the melting point or softening temperature of the thermoplastic composition and at a sufficiently high shear rate to disperse the thermoplastic composition in the soluble material; then, the molten mixture is cooled to below the melting point or softening temperature of the thermoplastic composition to form a solidified matrix containing particles of the thermoplastic composition; which is then separated from the soluble material.

[0090] The term "immiscible" is used to refer to a mixture of components that, when combined, form two or more separate phases.

[0091] The term "soluble" is used in its conventional sense to refer to a material that is capable of being dissolved.

[0092] In a preferred embodiment, the method comprises the following steps:

[0093] - mixing a mixture comprising a thermoplastic composition comprising at least one semi-aromatic polyamide as defined above and a soluble material immiscible with the thermoplastic composition at a temperature greater than the melting point or glass transition temperature of the thermoplastic composition and at a sufficiently high shear rate to disperse the thermoplastic composition in the soluble material immiscible with the thermoplastic composition;

[0094] - cooling the mixture to below the melting point or glass transition temperature of the thermoplastic composition to form solidified pellets, strands or paste comprising the thermoplastic composition dispersed in the soluble material; and

[0095] - contacting these solidified pellets, strands or pastes with a solvent capable of selectively dissolving the soluble materials, obtaining a collection of particles consisting of the thermoplastic composition; and

[0096] -optionally drying the collection of particles.

[0097] The particles have an average particle size D(v,0.5) of 0.1 to 50.0 μm and a particle size distribution as defined by relation (I).

[0098] For the avoidance of doubt, the expression "soluble material" is used hereinafter to refer to a soluble material that is immiscible with the thermoplastic composition.

[0099] The soluble material is not particularly limited, provided that it can be processed at a temperature greater than the melting point or glass transition temperature of the thermoplastic composition and that it can be dissolved by a solvent that cannot dissolve the thermoplastic composition. The soluble material is preferably a material that can be melted or softened at a temperature that allows the thermoplastic composition to melt or soften (for example, at 100° C. to 300° C.). In addition, the soluble material can be kneaded with the thermoplastic composition and form a separate phase when in a molten or solidified state.

[0100] In a preferred embodiment, the soluble material is a water-soluble material. Examples of such water-soluble materials include, but are not limited to, sugars, including monosaccharides, oligosaccharides, polysaccharides, sugar alcohols, polydextrose, maltodextrin, and inulin; and water-soluble resins. Among water-soluble polymers, linear polymers with hydrophilic groups such as -O-, -CONH-, -COOH, or -OH can be mentioned. Examples include polyacrylamide, poly(acrylic acid), poly(methacrylic acid), poly(itaconic acid), poly(vinyl alcohol), poly(ethylene oxide) and copolymers thereof, poly(propylene oxide) and copolymers thereof, and polyesters comprising repeating units derived from alkylene oxide. Each of these water-soluble materials can be used alone or in combination.

[0101] In a preferred embodiment, the soluble material is selected from the group consisting of water soluble polymers. More preferably, the water soluble material is selected from the group consisting of poly(ethylene oxide), copolymers thereof and polyesters comprising repeating units derived from alkylene oxide.

[0102] Poly(ethylene oxide) suitable for the process of the invention typically has a number average molecular weight Mn in the range of 2,000 to 200,000 g / mol, preferably 15,000 to 150,000 g / mol. Favorable results have been obtained with poly(ethylene oxide) having a molecular weight Mn in the range of 15,000 to 45,000 g / mol.

[0103] Examples of water-soluble polyester polymers comprising repeating units derived from ethylene oxide include polyesters comprising repeating units derived from:

[0104] - at least one dicarboxylic acid component, and

[0105] - at least one diol component, wherein at least 2 mol % of the diol component is a poly(alkylene oxide) of the formula: H(OC p H 2p ) q -OH, wherein p is an integer from 2 to 4, preferably p is 2, and q varies from 2 to 10.

[0106] Suitable polyesters may additionally comprise repeating units derived from difunctional monomers containing at least one SO3M group attached to an aromatic moiety, wherein M is H or a metal ion selected from the group consisting of sodium, potassium, calcium, lithium, magnesium, silver, aluminum, zinc, nickel, copper, palladium, iron, and cesium, preferably selected from the group consisting of sodium, lithium and potassium. These functional groups are carboxyl groups. Illustrative examples of such polyesters are those commercially available from Eastman under the trade name AQ polymers, especially those having a glass transition temperature ranging from about 25°C to about 50°C. Most preferred is Eastman AQ 38S, which is a polyester identified as a diethylene glycol / cyclohexanedimethanol / isophthalate / sulfoisophthalate polyester, or Eastman AQ 48, which is a sulfopolyester.

[0107] The amount of soluble material in the mixture with the thermoplastic composition can be 30 wt% to 95 wt%, 35 wt% to 85 wt%, or even 40 wt% to 80 wt%, based on the total weight of the mixture.

[0108] Good results in terms of particle size and particle size distribution were obtained when processing a 50:50 weight ratio of polyamide comprising repeating units of formula 9T to poly(ethylene glycol) having a molecular weight of 30,000 to 45,000 g / mol.

[0109] In the case where the thermoplastic composition contains additives or additional thermoplastic polymers in addition to the semi-aromatic polyamide, these additives or additional thermoplastic polymers can be added to the mixture before melt mixing with the immiscible materials is carried out. These additional components can be mixed with the semi-aromatic polyamide physically or in a melt blending device. These additional components can be blended with the thermoplastic polymer just before making the mixture or well in advance.

[0110] More generally, the step of mixing the mixture of thermoplastic composition and soluble material can be carried out with any suitable device. An endless screw mixer (endless screw mixer), agitator mixer or twin screw extruder compatible with the temperature required for the molten mixture can be used. The amount of energy applied to this step can be adjusted to control the size of the particles obtained therefrom. Those skilled in the art can adjust the equipment (e.g., screw geometry) and the parameters (e.g., rotational speed) of the equipment to obtain particles of desired size.

[0111] The expression "mixed mixture" when relating to the thermoplastic composition and the soluble material covers the case where the mixture is prepared in an apparatus separate from the apparatus where the mixing step is performed as well as the case where the apparatus is the same apparatus.

[0112] According to the embodiment:

[0113] - in case a semicrystalline semiaromatic polyamide is used, the mixing step is carried out at a temperature chosen to be at least 10°C above the melting temperature (Tm) of the polymer or of the thermoplastic composition comprising the semicrystalline semiaromatic polyamide, for example at least 15°C or 20°C above Tm,

[0114] In case an amorphous semi-aromatic polyamide is used, the mixing step is carried out at a temperature chosen to be at least 50° C. above the glass transition temperature (Tg) of the amorphous polymer or of the thermoplastic composition comprising the amorphous semi-aromatic polyamide.

[0115] According to a preferred embodiment, the mixing step is performed at a temperature above 250°C, such as above 260°C, above 270°C or above 280°C.

[0116] The mixing step is typically conducted at a temperature below the temperature at which the thermoplastic composition begins to decompose.

[0117] The step involving processing the mixture into pellets, strands or paste may be performed by extrusion through a die.

[0118] The steps of mixing and processing into pellets, strands or paste are preferably carried out in an extruder equipped with an extrusion die.

[0119] The cooling step is carried out by any suitable means, at a temperature below 80° C., for example below 50° C. Mention may be made notably of air cooling or of quenching in a liquid, for example in water.

[0120] The stage of contacting the pellets, strands or paste with a solvent capable of selectively dissolving the soluble material may comprise a step of immersing it in one or more baths containing the selected solvent. The solvent, preferably water, is optionally heated to a temperature of up to 95° C., for example to a temperature of about 40° C., about 60° C. or about 80° C. The solvent, in particular when it is water, may also be supplemented with an acid or base, for example selected from the group consisting of potassium hydroxide, sodium hydroxide, lithium hydroxide, potassium carbonate, sodium carbonate, lithium carbonate, organic amines, hydrochloric acid and sulfuric acid. This step makes it possible to promote the dissolution or dispersion of the soluble material so as to recover the pellets of the thermoplastic composition.

[0121] The steps of the method of the present invention can be performed batchwise or continuously.

[0122] According to an embodiment, the steps of cooling the pellets, paste or strands at a temperature below 80°C, such as below 50°C, and contacting the pellets, paste or strands with a solvent, in particular water, such as by immersing the pellets or strands into the solvent, can be performed simultaneously in the same apparatus.

[0123] The method of the invention may also comprise an additional step of drying the granules, and / or an additional step of sieving the granules.The drying step may be carried out, for example, in a fluidized bed.

[0124] Use of particles for the manufacture of composite materials

[0125] The collection of particles of the invention is particularly suitable for preparing a composite material comprising continuous fibers and a matrix of a thermoplastic composition.

[0126] As used herein, the term "fiber" has its ordinary meaning as known to those skilled in the art, and may include one or more fiber materials suitable for reinforcing composite materials, which fiber materials may take the form of any of particles, flakes, whiskers, short fibers, continuous fibers, sheets, plies, and combinations thereof.

[0127] Therefore, a further object of the present invention is a method for producing a composite material comprising a fiber material of continuous fibers and a matrix comprising the thermoplastic composition detailed above, said method comprising:

[0128] i) immersing the fiber material in a bath containing an aqueous dispersion comprising an assembly of particles consisting of the thermoplastic composition that is the first object of the invention; and

[0129] ii) drying the fibrous material.

[0130] The step of impregnation of the fibrous material is carried out by passing the material through a continuous impregnation device comprising an impregnation tank containing an aqueous dispersion comprising the collection of particles as detailed above.

[0131] An assembly of particles consisting of the thermoplastic composition is mixed with water to form such a dispersion. The concentration of particles in the dispersion may vary and may be adjusted by one skilled in the art based on the amount of thermoplastic composition desired in the final composite material.

[0132] The fiber material is caused to circulate in a bath formed by an aqueous dispersion. The median size D(v,0.5) of the particles in the aqueous dispersion is 0.1 to 50.0 μm, so that they can penetrate into the fibers. Preferably, the median size D(v,0.5) of the particles is between 2.5 μm and 40.0 μm, preferably between 5.0 μm and 30.0 μm, or between 7.5 μm and 25.0 μm.

[0133] The median size D(v,0.5) of the particles can be conveniently selected as a function of the diameter of the fibrous material to be impregnated. The median size D(v,0.5) of the particles can advantageously be 1.0 to 4.0 times, or even 1.0 to 3.5 times, the average diameter of the fibrous material to be impregnated.

[0134] The distribution of particle sizes is such that the relationship (I), even (Ia) or (Ib) is satisfied. Without being bound by theory, it is believed that a particle size distribution that is tilted toward larger particle sizes, as represented by the relationship (I) between the D(v, 0.1), D(v, 0.5), D(v, 0.9) values ​​of the particle size distribution, is advantageous in the operation of the slurry impregnation process because it reduces the risk of foaming that may be caused by particles with smaller diameters when forming the slurry.

[0135] The aqueous dispersion (or slurry) containing the particle assembly may contain additional ingredients. These may be, for example, emulsifiers or dispersants to improve the stability of the slurry during the impregnation process.

[0136] The aqueous dispersion may also contain additives which need to be retained in the final composite material. Non-limiting examples are, for example, inorganic additives.

[0137] The pre-impregnated fiber material leaves the tank and is directed to a drying device for evaporating water. Any drying device can be used to evaporate water in this step.

[0138] The constituent fibers of the fibrous material can conveniently be selected from the group consisting of carbon fibers, glass fibers, basalt fibers, silica fibers, silicon carbide fibers, aromatic polyamide fibers. Fibers of plant origin can also be used. Mention may be made of natural flax, hemp, silk (especially spider silk), sisal fibers and other cellulosic fibers.

[0139] These constituent fibers may be used alone or in admixture.

[0140] The selected fibers can be single strands, multiple strands or a mixture of the two. In addition, they can have several geometric shapes. Therefore, they can be in the form of short fibers, and then produce a felt or nonwoven fabric in the form of strips, sheets, braids, rovings or fragments. Alternatively, they can be in the form of continuous fibers, unidirectional fibers (UD) or rovings or nonwoven fabrics for producing 2D fabrics. The constituent fibers of the fibrous material can also be in the form of a mixture of these reinforcing fibers with different geometric shapes. Preferably, the fiber is continuous.

[0141] Preferably, the fiber material consists of continuous fibers, in particular carbon fibers, of carbon, glass or silicon carbide or mixtures thereof.

[0142] Due to the size of the thermoplastic composition particles of the present invention, the thermoplastic composition is uniformly and evenly distributed around the fibers. In this type of material, the impregnated thermoplastic polymer must be distributed as evenly as possible in the fibers to obtain the minimum pores, i.e., the spaces between the fibers. The presence of pores in this type of material can act as stress concentration points, for example, when subjected to mechanical tensile stress, and then form fracture initiation points in the composite material, thereby causing mechanical weakening. The uniform distribution of the polymer matrix therefore improves the mechanical strength and uniformity of the composite material.

[0143] Typically, the volume percentage of the thermoplastic composition relative to the fiber material varies from 40% to 25%, preferably from 45% to 125%, and more preferably from 45% to 80%.

[0144] The composite materials obtained are semi-finished products in the form of strips or sheets with calibrated thickness and width for the manufacture of three-dimensional structural parts. They can be used to manufacture products in the following: transport sectors, such as automotive, aviation, marine or railways; renewable energy, in particular wind energy, hydrokinetic energy; energy storage devices, solar panels; thermal protection panels; sports and leisure equipment, health and medical equipment, smart devices; gas storage or transportation devices. The composite materials obtained by the process of the invention can be advantageously used for the manufacture of hydrogen storage or transportation tanks.

[0145] The above embodiments are intended to be illustrative rather than restrictive. Additional embodiments are within the inventive concept. In addition, although the present invention has been described with reference to specific embodiments, those skilled in the art will recognize that changes may be made in form and detail without departing from the spirit and scope of the present invention.

[0146] Examples

[0147] Material

[0148] PA9T: A semi-aromatic polyamide commercially available from Kuraray as GENESTAR GC98018. It is a 50:50 copolymer of 1,9-nonanediamine and terephthalic acid with 2-methyl-1,8-octanediamine and terephthalic acid.

[0149] PEG-1: Poly(ethylene oxide), Mn (about 35000 g / mol) (PolyglyKol 35000S, available from Clariant) was used as the soluble material

[0150] Example 1 - Preparation of particles using a melt emulsification method

[0151] A Leistritz co-rotating twin-screw extruder (D=18 mm; L / D=60) was used. Both the pellets of PA9T and the pellets of PEG-1 (50:50 weight ratio) were added to the first zone of the extruder and degassed using an open barrel in the ninth zone, with 10 heating zones used. The first heating zone was heated at 20°C, the second heating zone was heated at 270°C, and the third heating zone was heated at 290°C. A temperature of 290°C was applied until the last heating zone. The screw speed applied was about 200 rpm. The throughput was 8 kg / h, with 4 kg / h for each feeder. The resulting molten particles surrounded by molten PEG-1 were collected into a flask containing cold water to provide a slurry containing PA9T particles. The particles were recovered by centrifugation. Washing and centrifugation steps (1 to 5 times) were applied to remove PEG-1. The particles were then dried at 90°C.

[0152] The particle characteristics are summarized in Table 1 below.

[0153] Comparative Example 1

[0154] PA9T reactor flakes were ground using a Fluid Energy Model 4 Microfluidizer with a liquid nitrogen cooled material inlet. The mill was operated at a P1 inlet pressure of 621 kPa, a grinding pressure P2 of 414 kPa, and a feed rate of 0.5 kg / h. The resulting powder was collected and analyzed, with particle characteristics summarized in Table 1 below.

[0155] Particle size determination

[0156] The particle size distribution of the polymer powder is determined by a wet method using a MicroTrac S3500 laser diffraction instrument. The S3500 measures particle sizes in the range of 0.02 to 2,800 μm. The powders of Example 1 and Comparative Example 1 are dispersed in isopropanol. A laser beam is projected through a sample cell containing a stream of moving particles suspended in isopropanol. The light that hits the particles is scattered, and the scattered light is measured by a photodetector array. The photodetector array measures the amount of light (flux) at a specific angle. The electrical signal proportional to the measured flux value is then processed by a computer / software to form a multi-channel histogram of the particle size distribution. The particle size distribution by volume is reported in Table 1.

[0157] Table 1

[0158]

[0159] Particle aspect ratio

[0160] The powder samples of Example 1 and Comparative Example 1 were dispersed onto a carbon ribbon using a dispenser rod and then imaged by a variable pressure scanning electron microscope (SEM). The resulting image files were analyzed in ImageJ to measure particle length and width. Length was measured along the longest dimension of the particle, and width was measured along the shortest dimension of the particle.

[0161] The particle aspect ratio was calculated as length / width. A series of 10 particles were randomly selected from one image of each set of powder samples, where the length and width of each of these individual particles were measured. Finally, the mean and standard deviation of the aspect ratio parameter were calculated.

[0162] The particles of Example 1 had an aspect ratio of 1.1±0.1, indicating that the particles had a rounded quasi-spherical shape.

[0163] The particles of Comparative Example 1 had an aspect ratio of 1.7±0.5.

[0164] General procedure for preparing composite materials

[0165] A slurry-based impregnation method was used to produce unidirectional carbon fiber tapes impregnated with the polymer particles of Example 1 and Comparative Example 1.

[0166] Use unsized carbon fiber commercially available under the trade name TANSOME H2550 12K from Hyosung. They are supplied in the form of tows comprising 12,000 individual fibers. The individual fiber thickness is about 7 μm. A sufficient number of fibers are used to make a 76 mm wide unidirectional tape. Make the dry web of the collimated continuous fibers pass through a water bath containing water, polymer particles of Example 1 or Comparative Example 1, and a surfactant (Igepal CA-630, supplied by Sigma Aldrich).

[0167] At the start of the run, the water bath initially contained 297 g of polymer and 29.5 kg of water. A separate second tank was set up to contain 882.5 g of polymer, 4.4 g of surfactant, and 5.0 kg of water. This tank was used as a concentrated recharge tank for the first tank because the loss rate of polymer in the main aqueous bath during a typical slurry soaking process did not match the water loss rate. The recharge liquid flow from the recharge tank was pumped into the main slurry bath at a rate sufficient to maintain a target fiber volume fraction (Vf) of 0.60, as determined by weight checks throughout the run.

[0168] The line was allowed to equilibrate for 1.5 hours before collecting the prepreg tapes. After passing through the water bath, the web of collimated fibers was passed under a series of infrared lamps that promoted evaporation of the water and consolidation of the polymer. The tapes were then passed through a die heated to 340°C, then through a heated calender maintained at 120°C, and then through a series of cooling rollers before being wound onto a cardboard core. The line speed was set at 1.0 m / s. The prepreg tapes had a nominal fiber volume fraction of 0.60, which resulted in a final polymer content of 32 wt% and a fiber area weight of 124 g / m 2 .

[0169] Two tapes made from the particles of Example 1 and Comparative Example 1 were cut, mounted in epoxy, and polished in a manner that showed the cross-section of the tape. The polished tape pucks were then imaged using an optical microscope. The detailed sample preparation and imaging procedures are detailed below.

[0170] Sample preparation: Samples of UD tape were cut perpendicular to the fiber direction and then stabilized and coated with a two-component epoxy resin (e.g., Epoxicure 2 TM) is fixed. After curing, the disc is gradually ground and polished using sandpaper first and then diamond slurry on a felt pad. Sandpaper abrasives of 280 / P320 to 1200 / P4000 are suitable for initial grinding, and polishing can then be performed using diamond slurry with a particle size of 3.0 μm, then 1.0 μm, and finally 0.1 μm; a suitable slurry would be Diamond slurry from Electron Microscopy Sciences Diamond suspension series.

[0171] Imaging: Polished samples were imaged using an optical microscope at different magnification levels (100-300x).

[0172] The volume fractions of fibers, matrix, and pores were extrapolated via image analysis using ImageJ software. Color thresholding was gradually adjusted to obtain images of only black and white pixels, so that the pores (i.e., voids) remained black, and both fibers and matrix appeared white; this process was then repeated to produce images in which both pores and matrix were black and only fibers were white; the pixels in each resulting image were counted, allowing for simple calculation of the fraction of each component.

[0173] The tape made from Comparative Example 1 contained a relatively large amount of voids, resin rich regions, gaps / spaces within the tape width, and a highly inconsistent tape thickness across its width. The porosity was calculated to be about 10%.

[0174] In contrast, the tape made from Example 1 had uniform tape thickness across the tape width with very few gaps / spaces, and very uniform fiber distribution with minimal porosity or resin-rich regions. The porosity was calculated to be approximately 1%.

[0175] Laminate preparation and characterization

[0176] Composite laminates were prepared on a Rucks KV 275.11 upstroke press equipped with 600 mm × 600 mm, a maximum platen temperature of 450 ° C, and a maximum pressing force of 1000 kN. The tape was dried at 120 ° C for 18 h overnight and then annealed at 150 ° C for 10 min. The ply stack was wrapped in a Kapton (R) tape and sandwiched between aluminum sheets, and Zyvax composite Shield Release was applied. The prepared ply stack was loaded into a 18 cm × 28 cm tool and placed in a press. The prepared mold was then heated according to the program shown in Table 2.

[0177] Table 2

[0178] Temperature(℃) Pressure(kPa) Residence time (min) Step 1 320 400 2 Step 2 320 690 2 Step 3 320 1379 2 Step 4 320 2068 2 Step 5 320 2758 2 Step 6 150 400 5

[0179] Samples were cut from the resulting laminates and tested according to the ASTM standards shown in Table 3.

[0180] Table 3

[0181] Lay-up [0]6s [0]8s Resin Example 1 Comparative Example 1 <![CDATA[With fiber area weight (g / m 2 )]]> 124 124 Fiber volume fraction 0.61 0.61 0° flexural modulus (GPa) ASTM D7264 154±3 134±5 0° Maximum flexural stress (MPa) ASTM D7264 2040±183 1520±115 0° short beam shear strength (MPa) ASTM D2344 93.3±0.8 91.2±0.8

[0182] The composite laminates obtained from the polymer particles of Example 1 demonstrated significantly higher flexural modulus, maximum flexural stress, and short beam shear strength than the laminates made from the particles of Comparative Example 1.

Claims

1. A collection of particles, wherein the particles consist of a thermoplastic composition comprising at least one semi-aromatic polyamide; and wherein the particles have a volume-based median particle size D(v,0.5) of 0.1 to 50.0 μm and a particle size distribution such that the following relationship (I) is satisfied: (I) Where D(v,0.9) is the particle size below which 90% of the sample lies; D(v,0.5) is the particle size below which 50% of the sample lies and 50% of the sample lies above this size; and D(v,0.1) is the particle size below which 10% of the sample lies.

2. The particle assembly according to claim 1, wherein: The particle size distribution satisfies the following relationship (II): (II) 3. The particle assembly according to any one of claims 1 or 2, wherein: D(v,0.9) is 100.0 μm or less, 65.0 μm or less, 50.0 μm or less and / or D(v,0.1) is at least 1.0 μm, at least 2.5 μm, at least 5.0 μm.

4. A collection of particles as claimed in any one of the preceding claims, wherein: D(v,0.5) is 1.0 to 50.0 μm, 2.5 to 40.0 μm, preferably 5.0 to 30.0 μm, even 7.5 to 25.0 μm.

5. A particle collection as claimed in any one of the preceding claims, characterized in that The particle size distribution satisfies the following relationship:

6. A collection of particles as claimed in any one of the preceding claims, wherein: The semi-aromatic polyamide comprises repeating units of formula XT, wherein X represents a unit derived from an aliphatic diamine having 8 to 36 carbon atoms, preferably 8 to 14 carbon atoms, or it comprises repeating units of formula MXDZ, wherein Z represents a unit derived from a linear or branched aliphatic or alicyclic diacid having z carbon atoms, wherein z is an integer equal to or greater than 6, preferably from 6 to 36, and MXD is meta-xylene diamine.

7. A collection of particles as claimed in any one of the preceding claims, wherein: The semiaromatic polyamide is selected from the group consisting of PA 6T, PA 8T, PA Me8T, PA 9T, PA Me8T / 9T, PA 10T, PA 11T, PA 12T, PA 6T / 9T, PA9T / 10T, PA 9T / 11T, PA 9T / 12T, PA 6T / 10T, PA 6T / 11T, PA 6T / 12T, PA 10T / 11T, PA 10T / 12T, PA 11T / 12T, PA 10 / 6T, 6PA 10 / 9T, PA 10 / 10T, PA 10 / 11T, PA 10 / 12T, PA 11 / 6T, PA11 / 9T, PA 11 / 10T, PA 11 / 11T, PA 11 / 12T, PA 12 / 6T, PA 12 / 9T, PA 12 / 10T, PA 12 / 11T, PA12 / 12T, PA 610 / 6T, PA 612 / 6T, PA 910 / 6T, PA 912 / 6T, PA 1010 / 6T, PA 1012 / 6T, PA 610 / 9T, PA 612 / 9T, PA 910 / 9T, PA 912 / 9T, PA 1010 / 9T, PA 1012 / 9T, PA 610 / 10T, PA 612 / 10T, PA 910 / 10T, PA 912 / 10T, PA 1010 / 10T, PA 1012 / 10T, PA 610 / 12T, PA 612 / 12T, PA 910 / 12T,PA 912 / 12T, PA 1010 / 12T, PA 11 / 6T / 9T, PA 11 / 6T / 10T, PA 11 / 6T / 11T, PA 11 / 6T / 12T, PA 11 / 9T / 10T, PA 11 / 9T / 11T, PA 11 / 9T / 12T, PA 11 / 10T / 11T, PA 11 / 10T / 12T, PA 11 / 11T / 12T, PA 12 / 6T / 10T, PA 12 / 6T / 11T, PA 12 / 6T / 12T, 12 / 9.T / 10.T, PA 12 / 9T / 11T, PA12 / 9T / 12T, PA 12 / 10T / 11T, PA 12 / 10T / 12T,PA 12 / 11T / 12T, PA MXDT / 10T, PA MPMDT / 10T, PA BACT / 10T, PA BACT / 6T, PA BACT / 10T / 6T, PA MXD6, PA MXD10.

8. A collection of particles as claimed in any one of the preceding claims, wherein: The thermoplastic composition comprises at least one semi-aromatic polyamide and 0.1 wt % to 40.0 wt % of at least one additional component selected from the group consisting of a plasticizer, a filler, and an impact modifier.

9. A method for producing a collection of particles as claimed in any one of the preceding claims, the method comprising the steps of: - mixing a mixture comprising a thermoplastic composition comprising at least one semi-aromatic polyamide and a soluble material immiscible with the thermoplastic composition at a temperature greater than the melting point or glass transition temperature of the thermoplastic composition and at a sufficiently high shear rate to disperse the thermoplastic composition in the soluble material; - cooling the mixture to below the melting point or glass transition temperature of the thermoplastic composition to form solidified pellets, strands or paste comprising the thermoplastic composition dispersed in the soluble material; and - contacting the solidified pellets, strands or pastes with a solvent capable of selectively dissolving the soluble material, obtaining a collection of particles consisting of the thermoplastic composition; as well as - optionally drying the collection of particles.

10. The method of claim 9, wherein: The soluble material is a water-soluble material, which is preferably selected from the group consisting of: sugars, including monosaccharides, oligosaccharides, polysaccharides, sugar alcohols, polydextrose, maltodextrin, and inulin, polyacrylamide, poly(acrylic acid), poly(methacrylic acid), poly(itaconic acid), poly(vinyl alcohol), poly(ethylene oxide) and copolymers thereof, poly(propylene oxide) and copolymers thereof, and polyesters comprising repeating units derived from alkylene oxide.

11. The method according to claim 9 or 10, wherein: The water soluble material is poly(ethylene oxide) having a molecular weight Mn in the range of 15,000 to 45,000 g / mol.

12. The method according to any one of claims 9 to 11, wherein: The amount of the soluble material in the mixture with the thermoplastic composition is 30 wt % to 95 wt %, 35 wt % to 85 wt %, even 40 wt % to 80 wt %, based on the total weight of the mixture.

13. The method according to any one of claims 9 to 12, wherein: The semi-aromatic polyamide comprises repeating units of formula 9T, the soluble material is poly(ethylene glycol) having a molecular weight of 30,000 to 45,000 g / mol, and the thermoplastic composition comprising at least one semi-aromatic polyamide and the soluble material are in a weight ratio of 50:50 in the mixture.

14. The method of claim 13, wherein: The mixing step is performed at a temperature above 260°C, above 270°C or above 280°C.

15. A liquid composition comprising the collection of particles as claimed in any one of claims 1 to 8 and water.

16. A method for making a composite material comprising a fibrous material of continuous fibers and a matrix comprising a thermoplastic composition, the method comprising: i) immersing the fiber material in a bath containing an aqueous dispersion comprising the particle assembly according to any one of claims 1 to 8; as well as ii) drying the fibrous material.

17. The method of claim 16, wherein: The continuous fibers comprise continuous fibers selected from the group consisting of carbon fibers, glass, silicon carbide, basalt, silica, natural fibers, in particular flax or hemp, lignin, bamboo, sisal, silk, or cellulose, in particular viscose fibers.

18. The method of claim 16 or 17, further comprising: The step of preparing a collection of particles according to the method of claims 9 to 14.

19. A composite material comprising continuous fibers and a thermoplastic polymer matrix comprising a semi-aromatic polyamide, said composite material being obtained by the process as claimed in any one of claims 16 to 18.

20. Use of the composite material according to claim 19 in the manufacture of three-dimensional composite parts.

21. The use according to claim 20, wherein The production of the composite parts relates to the following fields: transportation, oil and gas, gas storage, civil aviation or military, navigation, railways; renewable energy, thermal protection panels; sports and leisure, smart devices, health and medical.

22. An article of manufacture comprising a gas storage and transport tank comprising the composite material of claim 19.

Citation Information

Patent Citations

  • Method of impregnating a fibrous textile material with a plastic resin

    US4292105A